Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Simplifying
6(x + 1) + 5 = 13 + -2 + 6x
Reorder the terms:
6(1 + x) + 5 = 13 + -2 + 6x
(1 * 6 + x * 6) + 5 = 13 + -2 + 6x
(6 + 6x) + 5 = 13 + -2 + 6x
Reorder the terms:
6 + 5 + 6x = 13 + -2 + 6x
Combine like terms: 6 + 5 = 11
11 + 6x = 13 + -2 + 6x
Combine like terms: 13 + -2 = 11
11 + 6x = 11 + 6x
Add '-11' to each side of the equation.
11 + -11 + 6x = 11 + -11 + 6x
Combine like terms: 11 + -11 = 0
0 + 6x = 11 + -11 + 6x
6x = 11 + -11 + 6x
Combine like terms: 11 + -11 = 0
6x = 0 + 6x
6x = 6x
Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x
Combine like terms: 6x + -6x = 0
0 = 6x + -6x
Combine like terms: 6x + -6x = 0
0 = 0
Solving
0 = 0
Couldn't find a variable to solve for.
This equation is an identity, all real numbers are solutions.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.